Antibiotic production in Streptomyces is organized by a division of labor through terminal genomic differentiation - Zhang, Z; Du, C; de Barsy, F; Liem, M; Liakopoulos, A; van Wezel, GP; Choi, YH; Claessen, D; Rozen, DE (American Association for the Advancement of Science, 2020)
One of the hallmark behaviors of social groups is division of labor, where different group members become specialized to carry out complementary tasks. By dividing labor, cooperative groups increase efficiency, thereby raising group fitness even if these behaviors reduce individual fitness. We find that antibiotic production in colonies of Streptomyces coelicolor is coordinated by a division of labor. We show that S. coelicolor colonies are genetically heterogeneous because of amplifications and deletions to the chromosome. Cells with chromosomal changes produce diversified secondary metabolites and secrete more antibiotics; however, these changes reduced individual fitness, providing evidence for a trade-off between antibiotic production and fitness. Last, we show that colonies containing mixtures of mutants and their parents produce significantly more antibiotics, while colony-wide spore production remains unchanged. By generating specialized mutants that hyper-produce antibiotics, streptomycetes reduce the fitness costs of secreted secondary metabolites while maximizing the yield and diversity of these products.